The roles of heme oxygenase-1 in renal disease - Zhai, Hongfu; Ni, Lihua; Wu, Xiaoyan (Frontiers in Nephrology, 2023)
Heme oxygenase (HO), a heat shock protein containing hemoglobin, is an important enzyme in heme catabolism. It is involved in cell homeostasis, anti-inflammatory, antioxidant, anti-apoptosis, immunomodulation, and other functions. It was expressed at a modest level in most normal tissues. When the body suffers from ischemia hypoxia, injury, toxins, and other nocceptive stimuli, the expression rises, which can transform the oxidative microenvironment into an antioxidant environment to promote tissue recovery from damage. In recent years, research has increasingly verified its value in a variety of human bodily systems. It is also regarded as a key target for the treatment of numerous disorders.With the advancement of studies, its significance in renal disease has gained increasing attention. It is thought to have a significant protective function in preventing acute kidney injury as well as relieving non-specific damage produced by a variety of chronic kidney illnesses, including diabetic kidney disease and hypertension nephropathy. Its protective mechanism includes anti-inflammatory, antioxidant, cell cycle regulation, apoptosis inhibition, hemodynamic regulation, and other aspects that have been proven in diverse animal models. Furthermore, as a protective factor, its potential therapeutic efficacy in renal disease has recently become a hot area of research. Although no medicine targeting HO has been employed in clinical trials to date, a great number of in vitro research have indicated its potential in disease treatment. In this review, we summarize the current research status on the production, mechanism, treatment of HO and its relationship with various renal diseases.